2014
DOI: 10.5935/abc.20140158
|View full text |Cite
|
Sign up to set email alerts
|

Focused Cardiac Ultrasound Using a Pocket-Size Device in the Emergency Room

Abstract: BackgroundCardiovascular urgencies are frequent reasons for seeking medical care. Prompt and accurate medical diagnosis is critical to reduce the morbidity and mortality of these conditions.ObjectiveTo evaluate the use of a pocket-size echocardiography in addition to clinical history and physical exam in a tertiary medical emergency care.MethodsOne hundred adult patients without known cardiac or lung diseases who sought emergency care with cardiac complaints were included. Patients with ischemic changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
1
25
0
Order By: Relevance
“…In German CPUs, these procedures also comprise standards in noninvasive imaging methods including echocardiography with TTE evaluation as a minimum requirement for at least unstable NSTE-ACS patients [4]. So far, echocardiography is still the first-line imaging modality in triaging cardiac disorders due to its nearly universal availability, potential use at the bedside and low cost [8,9,10,11,12,19,20,21]. Beside its mainstream ability of determining global and regional LV function as well as valvular morphology and function in real-time within minutes, its diagnostic impact within the CPU setting can be further enhanced by, for example, strain, tissue-Doppler, perfusion or speckle-track analysis [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In German CPUs, these procedures also comprise standards in noninvasive imaging methods including echocardiography with TTE evaluation as a minimum requirement for at least unstable NSTE-ACS patients [4]. So far, echocardiography is still the first-line imaging modality in triaging cardiac disorders due to its nearly universal availability, potential use at the bedside and low cost [8,9,10,11,12,19,20,21]. Beside its mainstream ability of determining global and regional LV function as well as valvular morphology and function in real-time within minutes, its diagnostic impact within the CPU setting can be further enhanced by, for example, strain, tissue-Doppler, perfusion or speckle-track analysis [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that this technology has an incremental diagnostic value to cardiologic clinical examination, by increasing the number of correct diagnosis and reducing the routine use of echocardiography. 7 …”
Section: Discussionmentioning
confidence: 99%
“…The specificity of sonographic findings of pulmonary embolism has been shown to be higher than the sensitivity . Right ventricular dilatation with D‐shaped left ventricle, right heart thrombus, McConnell's sign, and deep vein thrombosis can be detected by ultrasound examination performed with handheld devices. Echographic findings of absence of pleural sliding and presence of lung point may help in identification of pneumothorax and can be detected using handheld thoracic sonography …”
Section: Assessment Of Patients With Acute Dyspneamentioning
confidence: 99%
“…The usefulness of integrated lung–heart ultrasound evaluation to determine chest pain etiology is established but there is lack of standardized protocols. In patients with chest pain and no certain diagnosis, after assessment of the medical history, physical examination, and ECG, focused echocardiography with pocket‐size equipment may allow a prompt diagnosis and, consequently, an earlier initiation of the therapy …”
Section: Assessment Of Patients With Chest Painmentioning
confidence: 99%